Mutagenic effect of EMS and DES on Tenai (Setaria italica) in M1 generation - L. Mullainathan, I. Anittha, (Journal of Phytology, 2018)
Mutation breeding gives better results for crop improvement through genetic manipulations when compared to other conventional breeding techniques. The present work focused in order to find out the effect of chemical mutagens; EMS and DES on Setaria italica in M1 generation. The seeds of Tenai, variety CO(Te)7 treated with different concentration of EMS and DES. The LD50 was observed at 30mM in EMS and 40mM in DES. Selection studies were conducted to improve the yield and to generate genetic variability in different quantitative traits such as days to first bloom, plant height, number of leaves, number of nodes, length and breadth of ear head, 1000 seed weight and yield per plant. The results revealed that, all the parameters were decreased with increasing concentration in both EMS and DES, while days to first bloom was increasing with increasing concentration. According to the result all the parameters studied shows a negative direction towards crop improvement in M1 generation because of the stress caused by mutagenic treatment.